Unlocking Purchase Intention: The Role of Value, Brand Awareness, and e-WOM in the Café Industry - Nuryanto, Imam; Panjaitan, Roymon (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This study aims to empirically investigate the impact of café-relevant values (CRV) and brand awareness (BA) on electronic word-of-mouth (e-WOM) and purchase intention (PI) within the café industry. Additionally, it examines the mediating role of e-WOM in these relationships. The study employed a cross-sectional survey design, collecting data from 246 café customers in Central Java, Indonesia. Structural Equation Modelling (SEM) was used to analyse the relationships between CRV, BA, e-WOM, and PI. The results revealed that both CRV and BA had significant positive effects on e-WOM and PI. Furthermore, e-WOM partially mediated the relationship between CRV and PI, as well as between BA and PI, suggesting that e-WOM enhances the influence of value perceptions and brand awareness on purchase decisions. This study contributes to the existing literature on Service-Dominant Logic by exploring the interplay between perceived value, brand awareness, and e-WOM in the café sector, which has not been extensively examined in previous research. Given these findings, café managers should focus on enhancing perceived value and brand awareness through quality services and strategic brand communication to increase consumer engagement and purchase intentions. Future research should explore these relationships in other industry contexts and consider longitudinal approaches for deeper insights.